Defect-mediated carbon incorporation in the si(0 0 1) surface: role of stress and carbon-defect interactions - Sonnet, Ph; Stauffer, Louise; Selloni, Annabella; Kelires, Pantelis C. (My University, 2003)
We present a comparative theoretical study of carbon incorporation on the Si(001) surface with and without Si defects, such as parallel and perpendicular ad-dimers or dimer vacancies. The influence of different parameters such as surface reconstruction, local stress before and after carbon adsorption and carbon-defect interaction are investigated. We find that ad-dimers or dimer vacancies make carbon incorporation easier, which can be explained by taking the above parameters into account in a systematic and combined way. The energetic barrier found for the defect-free surface at the crossing of the second layer is substantially lowered or vanishes. The site located just below the defect (in the third or fourth layers in the ad-dimer and dimer vacancy cases, respectively) is favored, and the site located in the middle between two defects plays a particular role.
Keywords: Carbon; Computer simulation; Defects; Surface chemistry